The concept of the intellect: An encyclopaedic glance through al-Tabari, al-Ghazali, and Abduh - Mohammed Muneer'deen, Olodo Al-Shafi'i (2017)
It is historically evident that the main arguments regarding the intellect and revelation is basically about which of the two supersedes the other and which is more superior. This paper looks mainly at the concept and understanding of the intellect through some dictionaries and in the major works of the great scholars. The paper further delves into the cognates there are for the intellect in the Qur'an to strengthen the arguments of the scholars. The wok is encyclopaedic though, it should not be misconstrued as depending on solely on 'encyclopaedias' as it generally connotes; it is encyclopaedic in the sense that it deals with major works of the selected scholars.